1985
DOI: 10.1252/jcej.18.464
|View full text |Cite
|
Sign up to set email alerts
|

Residence-time distribution of air flow in a spray drying chamber.

Abstract: Residence-time distribution in a spray dryer is very useful for the analysis of drying of atomized droplets. Also, for better understanding of spray dryer performance, it is most desirable to obtain the air flow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Many models assume the droplets travel at the same velocitv* as the drying media. This assumption is reasonable based on studies such as those reported by Usui et al (1985), Sano (1989), andZhelev (1989). These authors have found that the Peclet number, the ratio of bulk mass transfer to difEusion mass transfer of the air, remains constant for a particular dryer regardless of the characteristic air velocity.…”
Section: Gay Flow Characteristicsmentioning
confidence: 75%
See 3 more Smart Citations
“…Many models assume the droplets travel at the same velocitv* as the drying media. This assumption is reasonable based on studies such as those reported by Usui et al (1985), Sano (1989), andZhelev (1989). These authors have found that the Peclet number, the ratio of bulk mass transfer to difEusion mass transfer of the air, remains constant for a particular dryer regardless of the characteristic air velocity.…”
Section: Gay Flow Characteristicsmentioning
confidence: 75%
“…Zhelev (1989) found that the mixing inside the central core flow approached full mixing. Usui et al (1985) studied the residence time of air without droplets inside the drying chamber and obtained comparable experimental and simulation results when modeling the flow as a series combination of piston flow and perfect mixing.…”
Section: Gay Flow Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…Residence times of air flowing in a spray-drying chamber, with and without liquid spray, have been measured by Keey and Pham (1977), Pinilla, et al (1984), and Usui, et al (1985b). Such results have often been reported and interpreted in terms of overall Peclet numbers.…”
mentioning
confidence: 99%